Editorial: Interiority as Relations - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2018)
Understanding the relations between human being and its environment is critical in our attempt to create an appropriate built environment. Interior as a discipline has a privilege to be in the intersection between subjective experience of human users and the physical manifestation of environment occupied by the human. Looking at interiority as a relational construct that occurs between the users and environment should be an essential basis for design practice. This issue of Interiority intends to explore various forms of relational construct that emerge in the interaction between space and the users and to identify possible challenges posed by such relations for spatial design practice.